2019
DOI: 10.5037/jomr.2019.10308
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implant Outcomes in Grafted Sockets: a Systematic Review and Meta-Analysis

Abstract: ObjectivesTo assess the treatment outcomes of the dental implants placed in the grafted sockets.Material and MethodsA search protocol was developed to evaluate the treatment outcomes of dental implants placed in the grafted sockets in terms of implant survival rates (primary outcome), marginal-bone-level (MBL) changes, clinical parameters (i.e., bleeding on probing, probing depth), occurrence of peri-implant diseases, and aesthetic outcomes (secondary outcomes). Randomized controlled clinical trials (RCTs), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
5
23
1
Order By: Relevance
“…Outcomes of clinical studies on the long-term survival rates of implants placed in augmented vs. pristine bone is still controversial. While some studies indicated comparable outcomes in terms of implant survival rates and marginal bone loss [ 11 , 12 , 13 , 14 , 15 ], other studies reported inferior results for implants placed in augmented sites [ 5 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of clinical studies on the long-term survival rates of implants placed in augmented vs. pristine bone is still controversial. While some studies indicated comparable outcomes in terms of implant survival rates and marginal bone loss [ 11 , 12 , 13 , 14 , 15 ], other studies reported inferior results for implants placed in augmented sites [ 5 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…4. Dental Implant Outcomes in Grafted Sockets: a Systematic Review and Meta-Analysis (Ramanauskaite et al [4])…”
Section: Resultsmentioning
confidence: 99%
“…The values accepted as a reasonable guideline for MBL are 1.5 mm for the first year following loading of the implant and 0.2 mm of additional loss for each subsequent year [ 37 ]. A recent literature review by Ramanauskaite et al [ 37 ], including 7 RCTs, reported MBL changes between implants placed into the naturally healed sites or the previously grafted sockets. Two of them revealed no significant difference [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%